An EU-GDPR-Based Privacy Assurance Framework for Data Processors in the Software Package Implementation Industry in India - Rajagopalan, Premnath; Silic, Dario (Global journal of Business and Integral Security, 2023)
In the context of global data protection standards, such as the EU-GDPR, India’s software package implementation industry encounters distinct challenges. This research delves into the hurdles faced by Indian software organizations when attempting to meet GDPR requirements and explores the alignment between their data processing practices and the mandates of the EU-GDPR and DPDP Act. Given the complexities of bridging European standards and Indian practices, the study aims to craft a privacy assurance framework tailored to India’s unique context. This proposed framework will specifically cater to data processors in the software package industry, addressing their dual need to satisfy EU clients while navigating Indian regulatory specifics. Through this research, a deeper understanding of GDPR compliance within the Indian package implementation sector will emerge, offering solutions to foster heightened data protection measures in line with global standards.